Increased Efficiency of Endocrine Procedures Performed in an Ambulatory Room - Clark, Nicholas (2013)
BACKGROUND: Thyroid and parathyroid procedures historically have been viewed as inpatient procedures. Due to advancements in surgical techniques, these procedures were transferred from the inpatient operating room (OR) to the outpatient OR at a single academic institution approximately seven years ago. The goal of this study is to determine whether this change has decreased turnover times and maximized OR utilization. METHODS: We performed a retrospective review of 707 patients undergoing thyroid (34%) and parathyroid (66%) procedures by a single surgeon at our academic institution between 2005 and 2008. Inpatient and outpatient groups were compared using student’s t-test, Chi-squared test or the Kruskal-Wallis test where appropriate. Multiple regression analysis was used to determine how patient and hospital factors influenced turnover times. RESULTS: Turnover times were significantly lower in the outpatient OR (mean 18 min, ± 0.7 min) when compared with the inpatient OR (mean 36 min ±1.4 min) (p<0.001). When compared by type of procedure, all turnover times remained significantly lower in the outpatient OR. Patients in both OR’s were similar in age, gender, and co-morbidities. However, inpatients had a higher mean ASA score (2.30 vs. 2.13, p<0.001) and were more likely to have an operative indication of cancer (23.1% vs. 9.2%, p<0.001). Using multiple regression, the inpatient OR remained highly significantly associated with higher turnover times when controlling for these small differences (p<0.001). CONCLUSION: Endocrine procedures performed in the outpatient OR have significantly faster turnover times leading to cost savings and greater OR utilization for hospitals.